Sweets for my sweet: modulation of the limbic system drives salience for sweet foods after deep brain stimulation in Parkinson's disease. Issue 3 (15th December 2021) - Steinhardt, Julia; Hanssen, Henrike; Heldmann, Marcus; Neumann, Alexander; Münchau, Alexander; Schramm, Peter; Rasche, Dirk; Saryyeva, Assel; Büntjen, Lars; Voges, Jürgen; Tronnier, Volker; Krauss, Joachim K.; et al.
Abstract : Background: An increase in body weight is observed in the majority of patients with Parkinson's disease (PD) who undergo deep brain stimulation (DBS) of the subthalamic nucleus (STN) although the mechanisms are unclear. Objectives: To identify the stimulation-dependent effects on reward-associated and attention-associated neural networks and to determine whether these alterations in functional connectivity are associated with the local impact of DBS on different STN parcellations. Methods: We acquired functional task-related MRI data from 21 patients with PD during active and inactive STN DBS and 19 controls while performing a food viewing paradigm. Electrode placement in the STN was localised using a state-of-the-art approach. Based on the 3D model, the local impact of STN DBS was estimated. Results: STN DBS resulted in a mean improvement of motor function of 22.6%±15.5% (on medication) and an increase of body weight of 4 kg within 2 years of stimulation. DBS of the limbic proportion of the STN was associated with body weight gain and an increased functional connectivity within the salience network and at the same time with a decreased activity within the reward-related network in the context of sweet food images. Conclusions: Our findings indicate increased selective attention for high-caloric foods and a sweet food seeking-like behaviour after DBS particularly when the limbic proportion of the STN was stimulated.